Die Zeitschrift für Theologie und Kirche — von ihrer Gründung bis zum Ersten Weltkrieg - Kaufmann, Thomas (Zeitschrift für Theologie und Kirche, 2003)
The ZThK was published from 1891 on as an organ for establishing a dialogue between Albrecht Ritschl's school, with its specific program of an historical-critical theology, and the reality of the Protestant church. This article reconstructs the motives for founding the journal and the circumstances surrounding its creation. In addition to the first main editor, Johannes Gottschick Wilhelm Herrmann, Julius Kaftan, Adolf Harnack and the publisher Paul Siebeck also had considerable influence on these motives and circumstances. The author of this article also takes a look at the changes made in the program of the ZThK during the transitional period when Martin Rade took over as editor (1906/7) and the continuation of the ZThK after the First World War.